Effect of growth temperature on the epitaxy strain relaxation and the tilt of InxAl1−x as graded layer grown by solid-source molecular beam epitaxy - Loke, Wan Khai (2013)
In this study, we investigate the effect of the molecular beam epitaxial growth temperature on the epilayer tilt and the strain relaxation in the InAlAs M-buffer layer when the In composition is varied linearly from 6 to 57% followed by an inverse grading to 52% where InAlAs is lattice-matched to InP. The samples grown at 420 and 500 °C have final epilayer tilts of 0.66–0.68° about the $[1\,\bar {1}\,0 ]$ axis towards $[\bar{1}\,\bar{1}\,0 ]$ , whereas the sample grown at 370 °C has a smaller tilt of 0.15° about the $[1\,\bar {1}\,0 ]$ axis but towards [1 1 0]. Cross-sectional transmission electron microscopy micrographs showed that the sample grown at 420 °C has the lowest dislocation density (6 × 106 cm−2) compared with those grown at 370 and 500 °C. The inversely graded layer in all samples was shown to be effective in reducing the strain that was accumulated during the forward graded layer. This resulted in close to fully relaxed epilayers (92–99%), which are necessary for the prevention of further occurrence of dislocation nucleation (an important criterion for subsequent device structure growth).